Conceptualising redundancy and flexibility towards supply chain robustness and resilience. Issue 12 (1st December 2020) - Mackay, Jonathon; Munoz, Albert; Pepper, Matthew
Abstract: As disruptions and uncertainty have become emergent themes within the supply chain literature, attention has shifted towards the choices enacted to combat the negative effects of disruptions. Extant research highlights the importance of system states – namely robustness and resilience – towards mitigating the probability and magnitude of disruptions, however, there appears to be a lack of conceptual guidance surrounding two popular strategies – redundancy and flexibility – that have been proposed to mitigate the impact of disruptions. To address this issue, we review and investigate contextual factors from empirical research that may offer insight into conceptual strategies that can be utilised to improve post-disruption system performance utilising a methodology based upon an abductive approach to conceptual theory building. In this paper published research on resilience and robustness in supply chains is considered, alongside research in other areas such as risk, systems theory, and ecology. Inference drawn from empirical research is often highly contextualised, but collectively highlights unique generalisable factors. Our research proposes four broad conceptual strategies – insurance, expediting, strategic adaptive capability and reconfiguration – that each uniquely serve to reduce the probability and magnitude of supply chain disruptions. Our research concludes that the difference in utility between redundancy and flexibility as means to enhance resilience and robustness is influenced by interactions between the supply chain, the disruption characteristics (inclusive of speed of onset and time horizon) and the decision maker.